Análisis frente a la percepción del tratamiento estético dental, en la población UAN sede Bucaramanga (2022)
Aesthetic veneers as aesthetic treatments, as an alternative for the restoration of the conservative upper anterior sector, present both indications and contraindications that favor or not both their status over time and their duration or stability, which affects the perception of satisfaction by the patient, which led the authors to ask what is the status of veneers as an aesthetic dental treatment and its perception in the population of the UAN headquarters in Bucaramanga